The barley genome sequence assembly reveals three additional members of the CslF (1,3;1,4)-β-glucan synthase gene family. - Miriam Schreiber; Frank Wright; Katrin MacKenzie; Pete E Hedley; Julian G Schwerdt; Alan Little; Rachel A Burton; Geoffrey B Fincher; David Marshall; Robbie Waugh; Claire Halpin (PLoS ONE)
An important component of barley cell walls, particularly in the endosperm, is (1,3;1,4)-β-glucan, a polymer that has proven health benefits in humans and that influences processability in the brewing industry. Genes of the cellulose synthase-like (Csl) F gene family have been shown to be involved in (1,3;1,4)-β-glucan synthesis but many aspects of the biosynthesis are still unclear. Examination of the sequence assembly of the barley genome has revealed the presence of an additional three HvCslF genes (HvCslF11, HvCslF12 and HvCslF13) which may be involved in (1,3;1,4)-β-glucan synthesis. Transcripts of HvCslF11 and HvCslF12 mRNA were found in roots and young leaves, respectively. Transient expression of these genes in Nicotiana benthamiana resulted in phenotypic changes in the infiltrated leaves, although no authentic (1,3;1,4)-β-glucan was detected. Comparisons of the CslF gene families in cereals revealed evidence of intergenic recombination, gene duplications and translocation events. This significant divergence within the gene family might be related to multiple functions of (1,3;1,4)-β-glucans in the Poaceae. Emerging genomic and global expression data for barley and other cereals is a powerful resource for characterising the evolution and dynamics of complete gene families. In the case of the CslF gene family, the results will contribute to a more thorough understanding of carbohydrate metabolism in grass cell walls.